A three-stage adversity coping model for Chinese athletes. Issue 2 (4th May 2017) - Zhang, Chun-Qing; Si, Gangyan; Chung, Pak-Kwong; Bu, Danran
ABSTRACT: In this article, the authors discussed the development of a three-stage model of adversity coping in which Chinese athletes were categorized into three stages: climb, plateau, and enlightened stage. Specific, stage-related sport psychology services are recommended in this model. Particularly, sport psychology practitioners are encouraged to assist climb-stage athletes with mental skills and achievement motivation and help coaches establish an empowering motivational climate. Rational emotive behavioral therapy (REBT) and acceptance and mindfulness skills are recommended to help plateau-stage athletes overcome irrational and negative beliefs and habits. Finally, sport psychology services provided to enlightened-stage athletes should focus on developing an appreciation of the meaning and value of a sporting career, as well as enhancing work-life balance.